Analisis Yuridis Pasal 66 Ayat (1) Undang-Undang Jabatan Notaris Terhadap Pengawasan Notaris - Qurratu Uyun Ramadani Zulkhainen (Faculty of Law Universitas Islam Indonesia, 2022)
This research departs from the large number of application data submitted to the Constitutional Court (Mahkamah Konstitusi, MK) regarding Article 66 paragraph (1) of Law no. 30 of 2004 on the Position of Notary and its amendments by Law no. 2 of 2014 (Undang-Undang Jabtasn Notaris, UUJN). At least since UUJN was promulgated, there have been 4 MK decisions related to this article, and the most recent is PMK No.16/PUU-XVII/2020. Application regarding Article 66 paragraph (1) UUJN regarding the phrase